Perilaku Penggunaan Obat Tradisional pada Ibu Nifas di Desa Sungai Kitano Kecamatan Martapura Timur Kabupaten Banjar - Faizah Wardhina; Fakhriyah Fakhriyah; Rusdiana Rusdiana (HB PRESS, 2019)
ABSTRACT Introduction: Traditional Medicine is a natural ingredient which is well known and believed by people as a mild treatment used in maintenance of health and in the prevention of illnes and well being. People in in Sungai Kitano still utilize that culture, include traditional medicine for postpartum maternal. Aims: This study aimed to know about desciption of behaviour in using traditional medicine among post partum maternal at Sungai Kitano Village. Method: The study aimed to determine the behavior of traditional medicine use for postpartum mothers in the Sungai Kitano Village By using descriptive type of research, the sample in this study were mothers who were postpartum and who had postpartum not more than 3 years and lived in the Sungai Kitano Village. Sample are 48 peoples, using total population. Result: Postpartum maternal who use traditional medicine during the puerperal period as much as (95.83%), types of traditional medicine that are widely used: herbal medicine 37 people (77.08%), a rajangan form of traditional medicine that is widely used: 28 people (58, 33%), the most widely used by drinking 31 people (64.58%), the most reason for using traditional medicine because of the customs / habits of their parents are 28 people (62.5%),who feels the benefit are 46 people (95.83%),and who has no side effects: 42 people (86.95%). Conclusion:Post Partum maternal in Sungai Kitano Village mostly use traditional medicine in rajangan form, which is drank because of the customs / habits of their parents and had felt its benefit. Suggested for maternal who is using traditional medicine for paying attention in how to use, especially in the process of making in order to keep its cleaning.